Dexmedetomidine Based Sedation for Post-surgery Critically Ill Adults: A Meta-analysis of Randomized Controlled Trials - Heng FAN; Yu ZHAO; Min SUN; Ji-Hui YE; Guo-Dong CHEN; Jian-Hua ZHU (Tehran University of Medical Sciences, 2017)
Background: Using dexmedetomidine (Dex) as a sedative agent may benefit the clinical outcomes of post-surgery patients. We reviewed randomized controlled trials (RCTs) to assess whether use of a Dex could improve the outcomes in post-surgery critically ill adults. Methods: We searched Medline, Embase, PubMed, and the Cochrane databases for RCTs comparing Dex with propofol or a placebo in post-operative patients, all included RCTs should be published in English before Jul 2016. Citations meeting inclusion criteria were full screened, and trial available data were abstracted independently and the Cochrane risk of bias tool was used for quality assessment. Results: Sixteen RCTs involving 2568 patients were subject to this meta-analysis. The use of a Dex sedative regimen was associated with a reduce delirium prevalence [odd ratio (OR):0.33, 95% confidence intervals (CI): 0.24-0.45, I2= 5%, P<0.001], a shorter the length of ICU stay [mean difference (MD): -0.60, 95%CI: -0.69 to -0.50, I2=40%, P<0.001] and the length of hospital stay [MD: -0.68, 95%CI: -1.21 to -0.16, I2=0%, P=0.01]. However, using of Dex could not shorter the duration of mechanical ventilation [MD: -10.18. 95%CI: -31.08-10.72, I2=99%, P=0.34], but could shorter the time to extubation in post-surgery patients [MD: -47.46, 95%CI: -84.63-10.67, I2=98%, P=0.01]. Conclusion: The use of a Dex sedative regimen was associated with a reduce delirium prevalence, a shorter the length of ICU and hospital stay, and a shorter time to extubation in post-surgery critical ill patients.